Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s13717-021-00316-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of biodiversity gradient on plant mass and metabolism of individual submerged macrophytes

Abstract: Background The effects of biodiversity on community function and services are frequently studied in the history of ecology, while the response of individual species to biodiversity remains great elusive. In this study, we determined the biodiversity effects on community productivity as well as species level plant mass and carbon (C) and nitrogen (N) metabolism of eight submerged plants. These macrophytes in Lake Erhai were selected and planted in a water depth of one meter along a diversity gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
(90 reference statements)
2
3
0
Order By: Relevance
“…Generally, our experiment indicated that the two studied species responded differently to light, and even the different determined characteristics of the same species showed different responses to light ( Figs 1 and 2 ; Table 1 ). The results are in good agreement with the results of many former experiments due to the differences between species and the index specificity within a species ( Rae et al 2001 ; Hanelt et al 2006 ; Wu et al 2018 , 2020 ; Qi et al 2021 ). Our results highlighted that the plant mass, RGR, shoot height, ramet number (result because of trade-off between growth and reproduction) and leaf mass were significantly affected by high light although plant species explained most (>49 %) of the total variance in the above five measured indices ( Table 1 ).…”
Section: Discussionsupporting
confidence: 90%
“…Generally, our experiment indicated that the two studied species responded differently to light, and even the different determined characteristics of the same species showed different responses to light ( Figs 1 and 2 ; Table 1 ). The results are in good agreement with the results of many former experiments due to the differences between species and the index specificity within a species ( Rae et al 2001 ; Hanelt et al 2006 ; Wu et al 2018 , 2020 ; Qi et al 2021 ). Our results highlighted that the plant mass, RGR, shoot height, ramet number (result because of trade-off between growth and reproduction) and leaf mass were significantly affected by high light although plant species explained most (>49 %) of the total variance in the above five measured indices ( Table 1 ).…”
Section: Discussionsupporting
confidence: 90%
“…This might because that the LA of L. sativa is promoted by the low concentration of the aqueous extracts, in accord with former studies [35]. Overall, the different responses of the determined characteristics of the target species to the allelopathy is clearly due to their different sensitivity or the index specificity within a species [36][37][38]. In this study, our results showed that the leaves of A. philoxeroides from all of the sampling sites demonstrated strong allelopathic effects on the seed germination and seedling growth of the target species (Table 2).…”
Section: Plos Onesupporting
confidence: 71%
“…Different studied diversity indices are Shannon-Wiener Index (H'), Simpson's Index (D), Species Richness (R), and Evenness (E) gave the result as 3.451, 0.042, 33 and 0.946 respectively. The high diversity index represents the positive condition of wetlands as because of lower pollution percentage and less disturbance in the campus when compared to urban landscapes giving an opportunity to the macrophytes for better growth and development (Qi et. al., 2021, Li et.…”
Section: Resultsmentioning
confidence: 99%